TINJAUAN HUKUM PENJATUHAN PUTUSAN PIDANA TERHADAP PELAKU TINDAK PIDANA JUDI ONLINE - Deva Yurita; Sukmareni; Yenni Fitri Z (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This study analyzes the considerations by judges in imposing criminal decisions on perpetrators of online gambling crimes in Decision Number 111/Pid.B/2022/Pn Bkt. This research uses normative law research. Data analysis is used by interpreting the data and presenting it in sentences to answer problems in subsequent chapters. The results of this study are: 1) The panel of judges in deciding the considerations in the decision considers more juridical considerations that look at the defendant's background and life further. The judge should be able to give a more severe deterrent effect to the defendant, remembering the defendant is not just a number taker on gambling games online but acting as a bookie. 2) In imposing a criminal verdict, the public prosecutor and the Panel of Judges should also use the law on electronic transactions and information, considering that the defendant's case is online gambling, accessed using the network.